TRAINING ON THE DEVELOPMENT OF TEACHING MODULES FOR ENGLISH SUBJECTS BASED ON THE INDEPENDENT CURRICULUM FOR ENGLISH LANGUAGE STUDENTS - Rahayu, Gupuh; Devi, Rista Apriliya; Dhani, Arini Rahma; Bessie, Yoseph Ricardo (Universitas Muhammadiyah Lamongan, 2025)
The Merdeka Curriculum promotes a flexible, student-centered, and contextually grounded approach to learning, requiring educators to adapt their teaching strategies accordingly. English teachers, in particular, often encounter challenges in translating these principles into practical and effective learning modules. To address this gap, a workshop was conducted with the aim of enhancing participants' competence in developing English teaching modules that are both competency-based and aligned with the core values of the Merdeka Curriculum. The workshop engaged 120 students from the English Education Study Program, specifically those in their fifth semester, as prospective educators who will soon enter the teaching profession. Activities during the workshop included presentations, group discussions, and hands-on module design tasks. Evaluation methods involved pre- and post-workshop questionnaires to assess participants’ understanding and improvement in module development skills. The results indicated a significant increase in participants' ability to conceptualize, structure, and design interactive modules that incorporate the Merdeka Curriculum’s emphasis on autonomy, relevance, and learner engagement. In conclusion, the workshop successfully equipped future English teachers with practical tools and pedagogical strategies to develop effective teaching materials, thereby supporting the broader goals of educational reform in Indonesia.